2016
DOI: 10.2147/ijn.s98519
|View full text |Cite
|
Sign up to set email alerts
|

Study of the combined treatment of lung cancer using gene-loaded immunomagnetic albumin nanospheres in vitro and in vivo

Abstract: Combination therapy for lung cancer has garnered widespread attention. Radiation therapy, gene therapy, and molecular targeted therapy for lung cancer have certain effects, but the disadvantages of these treatment methods are evident. Combining these methods can decrease their side effects and increase their curative effects. In this study, we constructed a pYr-ads-8-5HRE-cfosp-iNOS-IFNG plasmid (a gene circuit that can express IFNγ), which is a gene circuit, and used that plasmid together with C225 (cetuximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Herein, we used 5 copies of the hypoxia responsive element (HRE) as an hTERT promoter enhancer (5HRE). The 5HRE element has previously been used as an enhancer to utilize the hypoxic microenvironment ( 39 ). Harvey et al ( 40 ) developed a hypoxia-targeted gene therapy strategy using the herpes simplex virus thymidine kinase and bacterial nitroreductase pro-drug-activating genes and showed that 5HRE linked to the CMV minimal promoter could induce optimum luciferase reporter gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we used 5 copies of the hypoxia responsive element (HRE) as an hTERT promoter enhancer (5HRE). The 5HRE element has previously been used as an enhancer to utilize the hypoxic microenvironment ( 39 ). Harvey et al ( 40 ) developed a hypoxia-targeted gene therapy strategy using the herpes simplex virus thymidine kinase and bacterial nitroreductase pro-drug-activating genes and showed that 5HRE linked to the CMV minimal promoter could induce optimum luciferase reporter gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin coating increased the yield of antisense oligonucleotides and siRNA transfection when used to coat positively charged liposomes [141] while decreasing their toxic effects. Similarly, Zhang et al [142] combined PEI-Fe3O4 magnetic nanoparticles with albumin via standard desolvation/cross-linking protocols to increase their biocompatibility, delivering more efficiently a plasmid to overexpress Interferon-γ in cancer cells. Figure 6 is a schematic representing the advantages of a surface functionalization based on albumin.…”
Section: Harnessing Endogenous Albumin and Hybrid Systemsmentioning
confidence: 99%
“…Emulated with adenovirus and lentivirus, AAV is rendered with more stable expression ability and higher immunocompatibility in nerve cells (Li and Samulski, 2020). The HRE can induce the expression of specific genes under hypoxic conditions (Schörg et al, 2015;Zhang et al, 2016). We used AAV to carry 5HRE-aFGF into NSCs and achieved a high expression of aFGF induced by hypoxia.…”
Section: Discussionmentioning
confidence: 99%